Isolation and digital counting of extracellular vesicles from blood via membrane-integrated microfluidics - Chen, Yi-Sin; Chen, Chihchen; Lai, Charles Pin-Kuang; Lee, Gwo-Bin (Sensors and actuators. B, Chemical, 2022)
Extracellular vesicles (EVs), existing in body fluids, have exhibited a significant potential in clinical diagnostics since many harbor biomarkers specific to certain diseases. Therefore, platforms capable of isolating EVs and quantifying these disease-associated proteins and nucleic acids are under current development. Herein, this study devised a membrane-based EV isolation/counting (mEVic) microfluidic platform that combined two membrane filters to carry out EV isolation from blood, followed by quantification of immuno-stained particles on a single chip. A 0.2-μm polycarbonate membrane was first used for small EV (sEV) isolation via stirring-enhanced filtration, and over 99% of sEV were isolated from only 2 μL of blood. For quantification, aluminum oxide membrane (20 nm)-based immunostaining with in situ fluorescent signal amplification was achieved to where fluorescence-labeled EVs could be individually visualized and counted under a microscope. The limit of detection of CD63 + EVs and PalmGRET EVs spiked in plasma was 105 EVs/mL. Moreover, the membrane-based EV staining assay was able to measure exosomal protein expression on single EVs. This new mEVic platform may therefore serve as a promising tool for isolating and quantifying specific EVs and could be integrated with fingertip-based disease diagnostic applications. •A membrane-based EV isolation/counting (mEVic) microfluidic platform was developed.•Small EV isolation was achieved (~99%) via stirring-enhanced filtration from only 2 μL of blood.•CD63 + EVs were fluorescently labeled, counted and quantified with LOD as low as 105 EVs/mL.